2015
DOI: 10.4103/0366-6999.170269
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Degree Centrality of Bilateral Putamen and Left Superior Frontal Gyrus in Schizophrenia with Auditory Hallucinations

Abstract: Background:Dysconnectivity hypothesis of schizophrenia has been increasingly emphasized. Recent researches showed that this dysconnectivity might be related to occurrence of auditory hallucination (AH). However, there is still no consistent conclusion. This study aimed to explore intrinsic dysconnectivity pattern of whole-brain functional networks at voxel level in schizophrenic with AH.Methods:Auditory hallucinated patients group (n = 42 APG), no hallucinated patients group (n = 42 NPG) and normal controls (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The results of the present study also showed that the hallucination severity was significantly negatively correlated with the GMV in the left SFG, supporting the previous reports that the left SFG is involved in hallucinations [ 68 , 74 ] and more in detail the GMV of the left SFG is significantly negatively correlated with severity of hallucination [ 68 ]. It has also been known that the left SFG plays a critical role in mediating working memory [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study also showed that the hallucination severity was significantly negatively correlated with the GMV in the left SFG, supporting the previous reports that the left SFG is involved in hallucinations [ 68 , 74 ] and more in detail the GMV of the left SFG is significantly negatively correlated with severity of hallucination [ 68 ]. It has also been known that the left SFG plays a critical role in mediating working memory [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…The observed association between nocturnal hallucinations and reduced basal ganglia volume was not surprising because nucleus accumbens and putamen are included in the limbic system and are responsible for psychiatric symptom production in PD [ 33 ] and schizophrenia [ 34 ]. Despite the lost significance after adjustment for bilateral putamen involvement, it can be suspected that putamen volume reduction can also be responsible for production of bad dreams These findings allow us to assume that if neurodegeneration starts in the nucleus accumbens then bad dreams turn into hallucinations, which are the hallmark of ongoing progression of cognitive decline [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each individualā€™s functional images were normalized using the symmetric echo-planar imaging templates and resampled at a resolution of 3 mm Ɨ 3 mm Ɨ 3 mm. The normalized functional images were smoothed spatially using a 6 mm full width at half maximum (FWHM) Gaussian kernel 23 . Finally, voxel-wise linear trend removal and temporal high-pass filtering (0.01 Hz < f < 0.08 Hz) were applied.…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…To eliminate possible spurious connectivity, we used the Pearson correlation coefficient at r > 0.25 by thresholding each correlation at P ā‰¤ 0.001 18 . Furthermore, standardized weighted DC maps were acquired by subtracting the mean value, and then dividing by the standard deviation within the whole gray matter mask 23 .…”
Section: Methods and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation